Non-Functioning Paraganglioma of the Urinary Bladder Treated by Transurethral Resection: Report of a New Case (Global Journal of Medical Research, 2018)
Paragangliomas are extra-adrenal tumors of the autonomic nervous system and may be found within the skull base, neck, mediastinum and periaortic region. Paragangliomas of the urinary bladder are rare, and nonfunctioning bladder paraganglioma is even rarer and not easily recognized. Histological examination is often key in leading to a definitive diagnosis. The current report presents a case of a 59year-old female with urinary bladder paraganglioma. The patient presented with only painless gross haematuria. A transitional cell carcinoma was suspected, but histological examination and immunohistochemistry of a transurethral resection specimen confirmed the correct diagnosis. In the present report, the clinical features, diagnosis, and management of nonfunctional paraganglioma of the urinary bladder are discussed.